2016
DOI: 10.1177/2151458516641162
|View full text |Cite
|
Sign up to set email alerts
|

Review of Postoperative Delirium in Geriatric Patients Undergoing Hip Surgery

Abstract: Postoperative delirium is a serious complication following hip surgery in elderly patients that can adversely affect outcomes in both hip fracture and arthroplasty surgery. Recently, the incidence of hip fracture in the Medicare population was estimated at approximately 500 000 patients per year, with the majority treated surgically. The annual volume of total hip arthroplasty is nearly 450 000 patients and is projected to increase over the next 15 to 20 years. Subsequently, the incidence of postoperative deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 48 publications
6
81
0
2
Order By: Relevance
“…Delirium (sometimes called 'acute confusional state') is characterised by disturbed consciousness, cognitive function or perception, which has an acute onset and fluctuating course. The incidence of post-operative delirium following hip fracture surgery has been estimated to be between 4% and 53%, and is the most common surgical complication for older people following surgery (Rizk et al, 2016). The consequences of experiencing delirium include higher mortality rates, hospital-acquired complications, persistent cognitive impairments, poor functional recovery after surgery and increased healthcare costs (Martocchia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Delirium (sometimes called 'acute confusional state') is characterised by disturbed consciousness, cognitive function or perception, which has an acute onset and fluctuating course. The incidence of post-operative delirium following hip fracture surgery has been estimated to be between 4% and 53%, and is the most common surgical complication for older people following surgery (Rizk et al, 2016). The consequences of experiencing delirium include higher mortality rates, hospital-acquired complications, persistent cognitive impairments, poor functional recovery after surgery and increased healthcare costs (Martocchia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Older people report less pain than their younger counterparts because of a variety of physiological, social and cultural reasons or language barriers (Keen et al 2017). Delirium is one reason which can have a profound effect on pain assessment and management (Rizk et al 2016). The BPS (2013) found that people over the age of 85 with poor cognitive performance were the most likely group to receive inadequate pain control in hospital.…”
Section: Online Archivementioning
confidence: 99%
“…Under-treatment of acute pain is more likely to occur in cognitively impaired older people (Rizk et al 2016, Swart et al 2017. Although acute pain assessment and management in older people with cognitive impairment presents specific challenges, nurses can dramatically improve care through the use of observational and behavioural pain assessment tools and timely administration of appropriate treatments.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…Elective surgery is an ideal approach to investigate the brain vulnerabilities predisposing to POD, since it allows neuroimaging examinations to be performed before surgery. However, individuals after nonelective surgery were a more frail population with increased risk of delirium and adverse long-term outcomes compared to the elective surgery ones, deserving further investigations (Rizk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%